Relationship between health care and tourism sectors to economic growth: the case of Malaysia, Singapore and Thailand - Cheah, Chan Fatt; Abdul Samad, Abdul Rahim (Universiti Putra Malaysia Press, 2018)
The objective of this study is to examine the relationship between health care and tourism sectors to economic growth in Malaysia, Singapore and Thailand. Panel ARDL test was employed to investigate their long- and short-run relationships by examining annual time series data from 1995-2016. Results show a significant positive short- and long-run relationship between development of healthcare and tourism sectors to economic growth in Malaysia, Singapore and Thailand. As stated in the ASEAN Tourism Strategic Plan 2016-2025, Malaysia, Singapore and Thailand should work together to promote ASEAN as a health tourism destination to the world.